The Enforcement of Defamation Law Regarding the Creation of a “Meme” Sticker on WhatsApp - Irawan, Joshua Evandeo; Valencia, Claresta Devina (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
Creating meme stickers on WhatsApp using photos of others has become a common trend. However, often the individuals depicted in these memes feel offended and argue that such actions defame their reputation. The article on defamation is regulated in Article 27 A paragraph (1) of Law 1/2024 (amendment to Article 27 of Law 11/2008). This research employs normative juridical research methods and finds that the act of creating meme stickers on WhatsApp does not constitute the offense of defamation under Article 27 A paragraph (1) of Law 1/2024 as it does not meet the elements of accusation. However, creating Meme Stickers using other people's faces fulfills the criteria outlined in Article 32 paragraph (1) of Law 11/2008, which is the Prohibition of Changing other people's entities without permission. This research will also examine the role of the National Criminal Code which serves as the Ius Constituendum of Criminal Law. Under the National Criminal Code, meme sticker makers on WhatsApp could be subject to the provisions of the Article of Light Insult, specifically in Articles 436, 441 and 440.